2017 International Conference on Cyberworlds (CW) 2017
DOI: 10.1109/cw.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

EEG-based Mental Workload and Stress Recognition of Crew Members in Maritime Virtual Simulator: A Case Study

Abstract: Many studies have shown that the majority of maritime accidents/incidents are attributed to human errors as the initiating cause. Efforts have been made to study human factors that can result in a safer maritime transportation. Among all techniques, Electroencephalogram (EEG) has the advantages such as high time resolution, possibility to continuously monitor brain states with high accuracy, recognition of human mental workload, emotion, stress, vigilance, etc. In this paper, we designed and carried out an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…That study concluded that only FD could be used to evaluate human mental workload. Several computational intelligence algorithms have been used to classify and detect mental workload levels, such as SVM [72,138,[190][191][192], ANN [193][194][195], and random forest (RF) [196].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…That study concluded that only FD could be used to evaluate human mental workload. Several computational intelligence algorithms have been used to classify and detect mental workload levels, such as SVM [72,138,[190][191][192], ANN [193][194][195], and random forest (RF) [196].…”
Section: Plos Onementioning
confidence: 99%
“…Emotions play an important role in overall human performance because they significantly affect cognitive functioning, decision-making, and individual performance [132,218]. Hence, understanding human feelings and emotions in the workplace is essential in providing safe working environments, especially in high-risk work such as maritime, aviation, and site construction [192,219]. Stress results from emotional pressure [220]; consequently, emotions and stress are tightly correlated [221].…”
Section: The Effect Of Emotion and Stressmentioning
confidence: 99%
“…Examples what can be studied to measure stress are salivary cortisol and heart rate (Main, Wolkow, and Chambers 2017;Main and Chambers 2015). Measuring electroencephalography (i.e., EEG) is also another method, which observes the electrical activity within the human brain for stress (Liu et al 2017). This, however, is an example of high resolutions achieved, but may not be as applicable to real-world experiments as, for example heart rate.…”
Section: Measuring Stressmentioning
confidence: 99%
“…Nevertheless, this method provides insight into the mind process, from which the cognitive load [4] and psycho-physical state (emotions) [16] of the participants can be understood. Noise in the raw data is induced by invasive multi-wire sensors; and procedures in which sampling of the participant's stress hormone cortisol [8] was found disturbing and stressful, affecting the clarity of the final results.…”
Section: Related Workmentioning
confidence: 99%